2008
DOI: 10.1636/t07-14sc.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the dispersal of spiders within agricultural fields and an adjacent mature forest

Abstract: A manipulative experiment was done in corn fields and their adjacent forests using enclosures that restricted access to ground-dwelling spiders. Enclosures were either closed from the adjacent habitat but open to ballooning and ground-dwelling spiders (using holes cut in the side of enclosures) or were open plots (controls). This allowed us to test the role of ballooning compared to cursorial dispersal of ground-dwelling spiders within these habitats. A reciprocal substrate treatment was included in which leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…As initially predicted, our small scale burned sites appeared to not impose major constraints for spider colonization allowing both cursorial and aerial immigration. While cursorial dispersal represents directional spider short distance travels [70] which probably took place through the soil surface and the resprouting foliage directly from adjacent unburned areas, aerial ballooning is a passive mechanism of distant and random dispersal through air currents [33], [71]. These colonization processes seem to have happened faster than our first sampling (one month after fire) could record, and hence we recommend that future researches perform samplings in an earlier period.…”
Section: Discussionmentioning
confidence: 77%
“…As initially predicted, our small scale burned sites appeared to not impose major constraints for spider colonization allowing both cursorial and aerial immigration. While cursorial dispersal represents directional spider short distance travels [70] which probably took place through the soil surface and the resprouting foliage directly from adjacent unburned areas, aerial ballooning is a passive mechanism of distant and random dispersal through air currents [33], [71]. These colonization processes seem to have happened faster than our first sampling (one month after fire) could record, and hence we recommend that future researches perform samplings in an earlier period.…”
Section: Discussionmentioning
confidence: 77%
“…Spiders are dominant generalist arthropod predators in most terrestrial ecosystems and can exert top-down control on invertebrate prey assemblages, making them important biocontrol agents in agroecosystems (Riechert and Bishop 1990, Young and Edwards 1990, Carter and Rypstra 1995. Their efficiency in biocontrol is also mediated by a variety of behavioral processes, including the timing of dispersal into agricultural habitats (Hibbert and Buddle 2008, Sackett et al 2009, Royauteá nd Buddle 2012, intraguild predation and cannibalism (Buddle 2002, Balfour et al 2003, and the tendency to consume multiple prey items beyond satiation (i.e., ''wasteful killing''; Maupin and Riechert 2001). Fortuitously, spiders have also become a model taxon for studying personality traits (Riechert and Hedrick 1993, Johnson and Sih 2005, Pruitt et al 2008, Kralj-Fišer and Schneider 2012, Royaute´et al 2014) and personality differences are widespread across more than a dozen families of spiders (reviewed in Pruitt and Riechert 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the method used in the current study is more efficient for sampling ground active species (CHURCHILL 1993), which are the species that are most likely to colonize burned sites. Experimental evidence from agroecosystems has shown that active ground-dwelling spiders are efficient colonizers of new habitats, and are able to invade recently disturbed areas from both adjacent and distant habitat sources (e.g., HIBBERT & BUDDLE 2008). Additionally, MARTINS et al (2004) showed that the abundance of a sun spider (Solifugae) increased immediately after burning in a cerrado site, but this difference vanished 3-4 months later.…”
Section: Discussionmentioning
confidence: 99%